The effect of nanoclay filler loading on the flexural strength of fiber-reinforced composites - Vajihesadat Mortazavi; Mohammad Atai; Mohammadhossein Fathi; Solmaz Keshavarzi; Navid Khalighinejad; Hamid Badrian (Dental Research Journal, 2012)
Background: Flexural strength of prosthesis made with dental composite resin materials plays an important role in their survival. The aim of this study was investigating the effect of nanoclay fillers and Poly (methyl methacrylate)-grafted (PMMA-grafted) nanoclay fillers loading on the flexural strength of fiber-reinforced composites (FRCs). Materials and Methods: Standard FRC bars (2 Χ 2 Χ 25 mm) for flexural strength testing were prepared with E-glass fibers and a synthetic resin loaded with different quantities of unmodified nanoclay and PMMA-grafted nanoclay filler particles (0% as control group, 0.2%, 0.5%, 1%, 2%, 5%). Flexural strength and flexural modulus were determined. The data were analyzed using 2-way, 1-way ANOVA and post hoc Tukey′s test (α = 0.05). The fracture surfaces were evaluated by Scanning Electron Microscopy. Results: For groups with the same concentration of nanoparticles, PMMA-grafted filler-loaded group showed significantly higher flexural strength, except for 0.2% wt. For groups that contain PMMA-grafted nanoclay fillers, the 2% wt had the highest flexural strength value with significant difference to other subgroups. 1% wt and 2% wt showed significantly higher values compared to control (P < 0.05). None of the unmodified nanoclay particles loaded group represented statistically higher values of flexural strength compared to control group (P > 0.05). Flexural modulus of 2%, 5% wt PMMA-grafted and 0.5%, 1%, 2%, 5% wt unmodified nanoclay particles-loaded subgroups decreased significantly compared to control group (P < 0.05). Conclusions: PMMA-grafted nanoclay filler loading may enhance the flexural strength of FRCs. Addition of unmodified nanoparticles cannot significantly improve the flexural strength of FRCs. Addition of both unmodified and PMMA-grafted nanoclay particles in some concentrations decreased the flexural modulus.